Partilha de recursos por espécies simpátricas de anfíbios anuros, centro-oeste do Brasil. - Gambale, Priscilla Guedes (2016)
The amphibians have been excellent models to understand the resource partitioning patterns in biological communities. The main and most studied dimensions of resource partitioning are spatial, period of vocalization and diet. In anurans, another dimension that has been studied is the acoustic space.We evaluated the differential use in acoustic space of three anurans species, genus Physalaemus, occurring in sympatric that have similar ecological and phylogenetic characteristics, co-occurring in nine water bodies at Goiás state. We observed that the call structure's dimension is the most important to segregation of species, compared with the micro-habitat and period structure's dimension of species involved. However, the coexistence of species must be explained from the interactions of all dimensions involved. We tested the difference in food item's composition between the two sympatric species of Physalaemus. In this other niche's dimension, we concluded that despite the high overlap, the different food item's composition can ensure segregation in the habitat, and the common consumption is due to no prey's limitation. Ingestion of different preys' volumes can also serve as a form of predator's segregation.